Perceptions of progress and assessment in non-linear, student-led, task-based adult courses in a private language institute in Portugal - Priestley, Karen (2017)
Task-based language teaching (TBLT) promises natural, efficient language acquisition through meaningful communication reflecting real-world interaction, while task-based assessment (TBA) evaluates performance in communicative tasks. Neither is without critics, and the implementation of both TBLT and TBA signifies opportunities and challenges. This research investigates learner and teacher perceptions towards adult learner progress on non-linear, student-led, task-based courses in northern Portugal, exploring what factors are perceived as influencing learner performance in assessed tasks, and asking to what extent navigation through non-linear, task-based lessons is perceived to prepare learners for external English examinations. Data was collected through a mixed methods approach, ninety-eight participants completing questionnaires and thirteen participants attending subsequent focus groups. The findings show that students and teachers are happier with perceived progress in some aspects of English than others. Among students, task topic and type influence task performance, while lesson materials and class size are key influences among teachers. Assessment procedures, but not level progression, are understood, and potential examination students expressed more happiness with perceived progress than students overall. Possible implications of these findings are also discussed, as are measures to address the issues identified.